Embodied Decision-Making Style: Below and Beyond Cognition - Connors, Brenda L.; Rende, Richard (Frontiers in Psychology, 2018)
ABSTRACT There is growing recognition of the essential role of sensorimotor processes as not just a supporter of the cognitive aspects of decision making, but rather as a foundation for all the coordinated physical and mental activities that go into how we make decisions. We illuminate concepts and methods for examining embodied decision making through the lens of Movement Pattern Analysis (MPA). MPA is as a prime example of a conceptually rooted observational methodology for deciphering embodied decision making and for decoding how people differ as decision makers with respect to cognitive motivational priorities. The historical origins of MPA that predated the formalized recognition of embodied cognition are presented, along with an overview of both the theoretical model and methodology. Advances in research on two psychometric benchmarks of observational research – inter-rater reliability and predictive validity – are highlighted as an empirical platform for the strong promise of MPA as a tool for understanding individual differences in embodied decision-making style. Future directions for research are considered – specifically with respect to the potential for utilizing automated coding, and the need for collaborative neuroscience research efforts – which would support further understanding of how decoding movement patterning captures human motivation at the level of sensory, motoric, cognitive and action integration which drives how people function as decision makers.